ChemInform Abstract: Tempering the Reactivities of Postulated α‐Oxo Gold Carbenes Using Bidentate Ligands: Implication of Tricoordinated Gold Intermediates and the Development of an Expedient Bimolecular Assembly of 2, 4‐Disubstituted Oxazoles. Issue 14 (20th March 2013) - Luo, Yingdong; Ji, Kegong; Li, Yuxue; Zhang, Liming
Abstract A variety of oxazole derivatives is prepared from terminal alkynes and carboxamides via a gold‐catalyzed oxidation strategy.